On Shi and Lun: toward a typology of historiography in the PRC - Weigelin-Schwiedrzik, Susanne (History and theory, 1996)
The discussion of shi and lun is the discussion of the relationship between historical data on the one side and theories of history on the other. It is the only methodological discussion historians in the PRC have been going through since the People's Republic of China (PRC) was founded in October 1949. The question of how to relate data to theory gained a new dimension as not only the quality of historical research but also historians' loyalty to the Communist regime was evaluated according to the methodological approach they preferred. In this article the political aspect of discussions of historiography in the PRC is left aside; here the discussion of the relationship between data and theory is used to develop a typology of Marxist historiography in the PRC. This discourse is characterized by three "slogans": theory has to take the lead over data (yi lun dai shi); data and theory have to be combined (shi lun jiehe); and interpretation has to emerge from data (lun cong shi chu). The theory-oriented first slogan coincides with a way of writing history in which data are used to show the plausibility of Marxist theory. In contrast to this, the slogan demanding the combination of data and theory is aimed at finding the specific laws governing the historical process in China by applying Marxism as a kind of methodology to Chinese history, whereas the third idea of having interpretations emerge from the data is based on the idea of probing the quality of Marxism by having interpretations come out of historical research which might or might not prove to be compatible with Marxism. The typology suggested in this article results from discussions with both the "European" and the Chinese. By borrowing from both Hayden D. White and Jorn Rusen on the one side, and by introducing on the other side the debate Chinese historians have been carrying on, a solution is found that is specific with regard to answers concerning Marxist historiography in China, but which might be of further interest insofar as the method of establishing this typology might be of broader use when trying to understand historiography organized around philosophical concepts rather than plot structures borrowed from literature.